Antibacterial, Antifungal and Ecotoxic Effects of Ammonium and Imidazolium Ionic Liquids Synthesized in Microwaves - Fojtášková, Jana; Koutník, Ivan; Vráblová, Martina; Sezimová, Hana; Maxa, Milan; Obalová, Lucie; Pánek, Petr (Molecules, 2020)
Ionic liquids are increasingly used for their superior properties. Four water-immiscible ionic liquids (butyltriethylammonium bis(trifluoromethylsulfonyl)imide, octyltriethylammonium bis(trifluoromethylsulfonyl)imide, dodecyltriethylammonium bis(trifluoromethylsulfonyl)imide, butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) and their water miscible precursors (bromides) were synthesized in a microwave reactor and by conventional heating. The best conditions for microwave-assisted synthesis concerning the yield and the purity of the product are proposed. The heating in the microwave reactor significantly shortened the reaction time. Biocide and ecotoxic effects of synthesized ionic liquids and their precursors were investigated. All tested compounds had at least a little effect on the growth or living of microorganisms (bacteria or mold). The precursor dodecyltriethylammonium bromide was found to be the strongest biocide, but posed a risk to the aquatic environment due to its relatively high EC50 value in the test with Vibrio fischeri. We assumed that apart from the alkyl chain length, the solubility in water, duration of action, or type of anion can influence the final biocide and ecotoxic effect.
Keywords: Microwaves; amoniové sloučeniny; Antifungal Agents; mikrovlny; Quaternary Ammonium Compounds; ekotoxikologie; Ecotoxicology; Aliivibrio fischeri; Anti-Bacterial Agents; kvartérní amoniové sloučeniny; Drug Evaluation, Preclinical; iontové kapaliny; Imidazoles; Ammonium Compounds; preklinické hodnocení léčiv; Ionic Liquids; antibakteriální látky; antifungální látky; imidazoly